032 Supine hypertension and cardiovascular autonomic failure in patients with alpha-synucleinopathies. Issue 9 (12th August 2022) - Vichayanrat, Ekawat; Koay, Shiwen; Ingle, Gordon; Hagen, Ellen Merete; McNamara, Patricia; Watson, Laura; Iodice, Valeria
Abstract : Introduction: Orthostatic hypotension (OH) and supine hypertension (SH) are prevalent in alpha-synucle- inopathies, posing a therapeutic dilemma as OH treatment may worsen SH. We aimed to characterise SH in pure autonomic failure (PAF), multiple system atrophy (MSA), and Lewy body disorders (LBD: Parkinson's disease and Dementia with Lewy bodies). Methods: 166 patients (72 PAF, 59 MSA, 35 LBD) underwent cardiovascular autonomic testing and 24hr- ambulatory blood pressure monitoring (24hr-ABPM). Demographic, clinical features, medications and cardiovascular autonomic biomarkers were compared. Results: SH was present in more than half of patients with PAF, MSA and LBD (56%, 51% and 50%, respec- tively) without anti-hypotensive medications. Supine pre-stand BP during 24hr-ABPM detected SH with 60% sensitivity and 86% specificity [area under the curve 0.73 (95%CI 0.66-0.81)]. Supine noradrenaline levels were significantly higher in MSA vs PAF and LBD (268 vs 183 and 210 pg/ml, p<0.01). There was a strong correlation between OH, SH and nocturnal hypertension after adjusting for age, anti-hypotensive medications and supine noradrenaline levels (R2=0.48, p<0.01). Conclusions: SH and nocturnal hypertension commonly co-exist and are independently associated with OH in alpha-synucleinopathies. 24hr-ABPM is useful in detecting SH in these patients. The pathophysiology of SH is likely to be heterogeneous and not entirely explained by residual sympathetic tone.